2014
DOI: 10.1093/nar/gku1356
|View full text |Cite
|
Sign up to set email alerts
|

DNA polymerase β deficiency leads to neurodegeneration and exacerbates Alzheimer disease phenotypes

Abstract: We explore the role of DNA damage processing in the progression of cognitive decline by creating a new mouse model. The new model is a cross of a common Alzheimer's disease (AD) mouse (3xTgAD), with a mouse that is heterozygous for the critical DNA base excision repair enzyme, DNA polymerase β. A reduction of this enzyme causes neurodegeneration and aggravates the AD features of the 3xTgAD mouse, inducing neuronal dysfunction, cell death and impairing memory and synaptic plasticity. Transcriptional profiling r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
137
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(148 citation statements)
references
References 106 publications
8
137
1
2
Order By: Relevance
“…Mice with Pol␤ heterozygosity have defects in mitochondrion-related pathways in the brain, including oxidative phosphorylation (25). Further, using large-scale mitochondrial extracts from bovine heart, a Pol␤-like activity has been reported (23).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Mice with Pol␤ heterozygosity have defects in mitochondrion-related pathways in the brain, including oxidative phosphorylation (25). Further, using large-scale mitochondrial extracts from bovine heart, a Pol␤-like activity has been reported (23).…”
Section: Resultsmentioning
confidence: 98%
“…For this experiment, we used brain tissue extracts from Pol␤ heterozygous (HT) mice. Pol␤ HT mice have accelerated age-related neurodegeneration, suggesting that the brain may be selectively affected by Pol␤ heterozygosity (25). WT mitochondrial samples (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Exhaustive research is undergoing in this field but still the enigma behind such progressive neuronal death is not well understood. Over the last several decades the studies have showed that the progression of neurodegenerative diseases involve the decreased antioxidant levels, impaired mitochondrial activity, increased oxidative damage protein, lipid peroxidation, protein modification, DNA damage and apoptosis [4][5][6][7][8][9] . Oxidative protein modifications occur at a low and persistent level in diverse cells and tissues and accumulate in aging and neurodegenerative diseases [10][11][12][13][14][15][16][17][18][19] .…”
Section: Reviewmentioning
confidence: 99%
“…Variant alleles of polymorphisms in the genes coding for human apurinic/apyrimidinic endonuclease APE1 (the main nuclease hydrolysing the phosphodiester backbone 5'-from the abasic site generated by BER glycosylases) and the gene coding for XRCC1, the stabilising factor of ligase III (the primary ligase of BER) were identified as predisposing factors for sporadic Parkinson's disease [138]. Deficiency of DNA polymerase beta was reported to accelerate cognitive decline in transgenic mice modelling AD [139].…”
Section: Don't Throw Away Repair It -Capacity To Repair Genotoxic Damentioning
confidence: 99%